2006
DOI: 10.1080/13664530600587311
|View full text |Cite
|
Sign up to set email alerts
|

‘It has always been my dream’: exploring pre‐service teachers’ motivations for choosing to teach

Abstract: This article reports on an investigation into the motivations of a cohort of pre-service teacher education students, undertaking a five-year, full-time combined undergraduate and initial teacher education degree program at the University of Sydney, Australia. Participants completed an extensive questionnaire which sought to gather data on the characteristics of the cohort; the factors that influenced their decision to undertake a teaching degree; their educational and work backgrounds; their perceptions of tea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
124
0
24

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 204 publications
(157 citation statements)
references
References 13 publications
9
124
0
24
Order By: Relevance
“…In a study on the Turkish prospective teachers' motivations for teaching, it was found that intrinsic career value, salary, societal status, societal influences, working with children/adolescents, and making social contribution were among the most significant factors that affected their choices for teaching (Y. Boz & N. Boz, 2008). Personal fulfillment, working with young people, working conditions, lifestyle, and professional status were found to be among the most influential factors affecting Australian prospective teachers' motivations for teaching (Manuel & Hughes, 2006). According to Wang (2004), prior teaching experiences, cultural beliefs about teaching, gaining social status, and favorable working conditions influence Taiwanese prospective teachers' motivations for teaching.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study on the Turkish prospective teachers' motivations for teaching, it was found that intrinsic career value, salary, societal status, societal influences, working with children/adolescents, and making social contribution were among the most significant factors that affected their choices for teaching (Y. Boz & N. Boz, 2008). Personal fulfillment, working with young people, working conditions, lifestyle, and professional status were found to be among the most influential factors affecting Australian prospective teachers' motivations for teaching (Manuel & Hughes, 2006). According to Wang (2004), prior teaching experiences, cultural beliefs about teaching, gaining social status, and favorable working conditions influence Taiwanese prospective teachers' motivations for teaching.…”
Section: Introductionmentioning
confidence: 99%
“…Spear, Gould, and Lee (2000) find in their review of research in England and Wales that intrinsic and altruistic motivations dominate the reasons for entering the profession among prospective teachers. Studies in Australia indicate that personal fulfillment, the desire to work with young children and to make a difference in their life and the opportunity to experience a meaningful engagement with the subject of their choice are the three main motivational factors (Manuel & Brindley, 2005;Manuel & Hughes, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Williams and Forgasz's (2009) findings from a study of motivations of 375 career change students support the research that people chose teaching as a career primarily for intrinsic or altruistic reasons rather than for extrinsic rewards such as pay, working conditions, career opportunities or status. Manuel and Hughes (2006) reported the quest for personal fulfillment, the desire to work with young people to make a difference in their lives, and the opportunity to continue meaningful engagement with the subject of their choice as fundamental reasons for people to choose teaching at the end of research with 79 secondary teacher education students in Australia. Anthony and Ord (2008) report push and pull factors, family experiences, values and task expectancies as the reasons of 68 participants to pursue teaching in New Zealand.…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…Researchers revealed that family interest, peer influence, cultural beliefs, role model and extrinsic reasons are part of the fundamental issues influencing student decision to choose teaching as a career [17,18,19,20]. Some of the factors cited varies across regions, for instance in Malaysia, cultural beliefs were identified to play a dominant role in facilitating the image of the teaching profession [21]; social influences were the key factors in the Turkish and Australian context); while socio-economic status was a significant factor in Zambia [22,23].…”
Section: What Is Expected Of a Professional Teacher?mentioning
confidence: 99%